Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1007/bf00171988
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of 4-demethoxydaunorubicin in previously untreated extensive disease non-small cell lung cancer

Abstract: Key words: non-small cell lung cancer, chemotherapy of lung cancer, 4-demethoxydaunorubicin, idarubicin, 4-DMDR, treatment of advanced lung cancer SummaryFifteen patients with previously untreated extensive non-small cell lung cancer (E-NSCLC) were treated with oral 4-demethoxydaunorubicin (4-DMDR) at the dose of 10 mg/m2/day x 5 days every 3 weeks with routine administration of antiemetic drugs. They received a median of two courses of treatment with the cumulative dose range from 50-712.5 mg/m 2. One patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…We repeated the analysis stratified by the decade of the study and anthracycline type; however, secular trends in the prevalence of arrhythmia in those studies were not observed. Prevalence estimates (ES) and confidence intervals (CIs) from studies with zero events were evaluated by adding 0.5 cases to both the numerator (number of anthracycline users) and the denominator (total number of arrhythmic events), consistent with the recommended practice [12,19,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Risk Of Arrythmia In Single-arm Studiesmentioning
confidence: 99%
“…We repeated the analysis stratified by the decade of the study and anthracycline type; however, secular trends in the prevalence of arrhythmia in those studies were not observed. Prevalence estimates (ES) and confidence intervals (CIs) from studies with zero events were evaluated by adding 0.5 cases to both the numerator (number of anthracycline users) and the denominator (total number of arrhythmic events), consistent with the recommended practice [12,19,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Risk Of Arrythmia In Single-arm Studiesmentioning
confidence: 99%